ta có: (a - b)2 = (a - b)(a - b) = a2 - ab - ab + b2 = a2 - 2ab + b2 (*)
ta có \(\frac{a^2+b^2}{c^2+d^2}=\frac{2ab}{2cd}\)
Áp dụng t/c của dãy tỉ số bằng nhau ta có: \(\frac{a^2+2ab+b^2}{c^2+2cd+d^2}=\frac{a^2-2ab+b^2}{c^2-2cd+d^2}\)
Áp dụng (*)
=> \(\frac{\left(a+b\right)^2}{\left(c+d\right)^2}=\frac{\left(a-b\right)^2}{\left(c-d\right)^2}\) Hay \(\left(\frac{a+b}{c+d}\right)^2=\left(\frac{a-b}{c-d}\right)^2\)
=> \(\frac{a+b}{c+d}=\frac{a-b}{c-d}\) hoặc \(\frac{a+b}{c+d}=-\frac{a-b}{c-d}\)
+) \(\frac{a+b}{c+d}=\frac{a-b}{c-d}\) => \(\frac{\left(a+b\right)+\left(a-b\right)}{\left(c+d\right)+\left(c-d\right)}=\frac{\left(a+b\right)-\left(a-b\right)}{\left(c+d\right)-\left(c-d\right)}\) => \(\frac{2a}{2c}=\frac{2b}{2d}\) => \(\frac{a}{b}=\frac{c}{d}\)
+) \(\frac{a+b}{c+d}=-\frac{a-b}{c-d}\) => \(\frac{\left(a+b\right)-\left(-\left(a-b\right)\right)}{\left(c+d\right)-\left(c-d\right)}=\frac{\left(a+b\right)-\left(a-b\right)}{\left(c+d\right)+\left(c-d\right)}\) => \(\frac{2a}{2d}=\frac{2b}{2c}\) => \(\frac{a}{b}=\frac{d}{c}\)